Characteristics contribution and similarity of F5 soybean lines resistant to cowpea mild mottle virus derived from different crossing - SITI ZUBAIDAH; HERU KUSWANTORO; EMERENSIANA UGE; KENNIS ROZANA; PURWANTORO PURWANTORO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Zubaidah S, Kuswantoro H, Uge E, Rozana K, Purwantoro. 2023. Characteristics contribution and similarity of F5 soybean lines resistant to cowpea mild mottle virus derived from different crossing. Biodiversitas 24: 5399-5408. Virus is one of the pathogens that can infect soybeans. One of the crucial viruses is Cowpea Mild Mottle Virus (CpMMV), which attacks many soybean plants in Indonesia. The objective of this study was to explore the character's contribution and similarity to identify F5 CpMMV-resistant soybean lines. The plant materials were F5 CpMMV-resistant soybean lines from 26 different crosses. CpMMV inoculation was performed naturally by placing the experiment at the site previously infected with Bemisia tabaci as the CpMMV virus vector. Observations were made on agronomic characters and disease scores. The results showed that there was a variation in the observed agronomic characters, but disease scores were generally at a score of 2. Seed yield, number of filled pods, and number of seeds showed strong character contributions. Disease scores generally had the opposite direction to seed size. There was a significant correlation between agronomic characters, but disease scores had no correlation with agronomic characters. M and N crosses showed the highest seed yields. The disease score for these two crosses was 2. These two crosses also formed a separate group. There were four groups of crosses with different numbers of members. The groups formed were more influenced by the variability of the number of seeds, filled pods, and plant height. Based on seed yield and disease score, M and N crosses should be further developed to obtain high-yielding CpMMV-resistant soybean varieties.